1989
DOI: 10.1029/jb094ib10p14127
|View full text |Cite
|
Sign up to set email alerts
|

Resistivity cross section through the Juan de Fuca Subduction System and its tectonic implications

Abstract: A resistivity cross section to depths exceeding 200 km has been derived from magnetotelluric observations along a profile near latitude 45øN from the Juan de Fuca spreading center, across the coastal subduction complex, the High Cascades volcanic arc, and into the back-arc Deschutes Basin region. In this two-dimensional interpretation, emphasis was placed on data approximating the transverse magnetic mode since these data are relatively robust to common departures from the two-dimensional assumption. The verti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
124
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 177 publications
(140 citation statements)
references
References 62 publications
15
124
1
Order By: Relevance
“…A lower crustal conductor beneath the aseismic front to the west in northeastern Japan has suggested the presence of H2O (e.g., Utada, 1987). Beneath the Oregon coast and Vancouver Island in North America, a high conductivity layer on the top of the descending Juan de Fuca plate has been observed, and lends itself to the inference of H2O-charged sediments that are partially subducted with the oceanic crust (e.g., Wannamaker et al, 1989;Young and Kitchen, 1989;Kurtz et al, 1990). A similar conductive layer has also been proposed in the Japan arc subduction zone by Utada (1987 …”
Section: Comparison With Heat Flow Temperaturementioning
confidence: 72%
“…A lower crustal conductor beneath the aseismic front to the west in northeastern Japan has suggested the presence of H2O (e.g., Utada, 1987). Beneath the Oregon coast and Vancouver Island in North America, a high conductivity layer on the top of the descending Juan de Fuca plate has been observed, and lends itself to the inference of H2O-charged sediments that are partially subducted with the oceanic crust (e.g., Wannamaker et al, 1989;Young and Kitchen, 1989;Kurtz et al, 1990). A similar conductive layer has also been proposed in the Japan arc subduction zone by Utada (1987 …”
Section: Comparison With Heat Flow Temperaturementioning
confidence: 72%
“…The experiment transect intersects the rifted marginal Otway basin, which is a few kilometres wide and deep (Williams and Corliss, 1982;Finlayson et al, 1994). The effect of brinesaturated sediments on the coast effect at subduction zones has been discussed by Kurtz et al (1986Kurtz et al ( , 1990 and Wannamaker et al (1989), but has not been observed at passive margins. For example, the models of White et al (1990) and Kellett et al (1991) for southeastern Australia gave a good fit of the observed data without the presence of sediment beneath the continental shelf and slope.…”
Section: Tectonic Interpretationmentioning
confidence: 99%
“…Thermal structure and chemical composition may lead to lateral variations in conductivity across the coastlines. At active continental margins in northwestern USA (Kurtz et al, 1986(Kurtz et al, , 1990Wannamaker et al, 1989) and Japan (Ogawa et al,1986) the subduction of fluids gives rise to a very marked lateral variation in upper mantle conductivity across the margin, but at passive margins there is less obvious reason for such a difference. In Fig.…”
Section: Sensitivity Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…We can additionally utilize the tipper function, which relates the horizontal magnetic field information to the vertical magnetic field. The relationship between these parameters can be expressed as in equation We generated models that inverted both the TM and TE modes, with error floors of 5% and 15% respectively, and a set of models using only the TM mode, which has been shown to be less influenced by, and therefore more robust to the effects of 3D structure (Wannamaker et al, 1989). The tipper function was included in both sets of inversions.…”
Section: Modelingmentioning
confidence: 99%